South Korea film-induced tourism: the K-drama determinant for Malaysian tourist - Saad, Mazni; Husin, Nor Azilah; Ramlee, Nur Zafirah (IGI Global, 2022)
This study surveyed 150 Malaysian tourists regarding the South Korean drama (K-drama) factors that drew them back to South Korea. The analyses revealed that K-drama was highly successful in enticing the young generation and discovered a clear scenario for Malaysians’ response for a repeat visit. The results show that collaboration for the development of heritage tourism should be linked to the national identity and replicated through dramas similar to K-dramas. Universities should work closely with other stakeholders to produce high-quality films for international distribution